Romantic relationships and adolescent depression in China: moderating effects of peer norms - Anqin Zhu; Anqin Zhu; Zeyu Kong; Aiping Zhou; Aiping Zhou (Frontiers in Psychiatry)
ObjectiveAdolescent depression is a crucial determinant of an individual’s developmental trajectories and long-term health-related quality of life. Romantic relationships are widely recognized as a risk factor of adolescent depression. Peer norms, as an important source of social influence in adolescence, have the potential to moderate the effects of romantic relationships. The present study aims to examine the moderating effects of peer norms, including descriptive norms and injunctive norms, on the association between romantic relationships and adolescent depression in China.MethodsThe present study used a nationally representative sample of 6718 junior high school students from the China Education Panel Survey (CEPS). The ordinary least squares regression model was used to assess both the main effects of romantic relationships on adolescent depression and the moderating effects of peer norms. The bounding approach was used for sensitivity analysis.ResultsRomantic relationships were positively associated with adolescent depression (β=0.290, p<.001). Descriptive norms, including class norms (β=-0.634, p=.042) and friend norms (β=-0.206, p<.001), significantly mitigate the association between romantic relationships and adolescent depression, but injunctive norms (β=0.253, p=.035) significantly exacerbate the association. The sensitivity analysis reveals that the above results are robust to the potential confounding impact of unobserved variables.ConclusionPeer norms were found to significantly moderate the correlation between romantic relationships and adolescent depression. It is important to play the role of descriptive and injunctive peer norms in the prevention and intervention for the depression of adolescents, especially for those who are in a romantic relationship.